Kemampuan Menulis Cerita Pengalaman dalam Bahasa Makassar Siswa SMP Negeri 1 Takalar - Ria Astuti Hamzah; Kembong Daeng; Hajrah Hajrah (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. This study aims to describe the ability to write experience stories in Makassar language for Grade VIII students of SMP Negeri 1 Takalar, Takalar Regency. This research is quantitative descriptive. The research variable is the ability to write experience stories in Makassar language for class VIII students of SMP Negeri 1 Takalar, Takalar Regency. The population in this study were students of class VIII SMP Negeri 1 Takalar and the research sample was students of class VIII 2 SMP Negeri 1 Takalar, Takalar Regency. The data collection technique used was a written test technique. Data analysis techniques according to Sugiyono, 2011: 49 namely: (1) making a list of raw scores, (2) making distributions of frequencies and average scores, (3) making tables of classifying student abilities. The results of this study indicate that students' scores on the ability to write experiential stories in Makassar language are inadequate because the average value of the entire sample is only 67.5 not achieving an ability score that is above 75 which shows that the sample obtaining a score of 75-100 totaled 11 students (35.48%) and the sample obtaining a score of 0-74 totaled 20 students (64.52%). This shows that the ability to write experiences in Makassar language, class VIII students of SMP Negeri 1 Takalar, Takalar Regency, are categorized as incapacitated. Keywords: Ability, Writing, Experience Stories, Makassar Language.